A discrete choice experiment to assess people living with HIV's (PLWHIV's) preferences for GP or HIV clinic appointments. (17th August 2016) - Miners, A H; Llewellyn, C D; Cooper, V L; Youssef, E; Pollard, A J; Lagarde, M; Sabin, C; Nixon, E; Sachikonye, M; Perry, N; Fisher, M
Abstract : Objectives: To understand which aspects of general practitioner (GP) and HIV clinic appointments people living with HIV (PLWHIV) most value when seeking advice for new health problems. Methods: A discrete choice experiment using a convenience sample of people diagnosed with HIV. Participants were recruited from 14 general HIV clinics in the South East of England between December 2014 and April 2015. ORs were calculated using conditional logit (CLOGIT) and latent class models (LCMs). Results: A total of 1106 questionnaires were returned. Most participants were male (85%), white (74%) and were men who have sex with men (69%). The CLOGIT analysis showed people particularly valued shorter appointment waiting times (ORs between 1.52 and 3.62, p<0.001 in all instances). The LCM analysis showed there were two distinct classes, with 59% and 41% of respondents likely to be in each. The first class generally preferred GP to HIV clinic appointments and particularly valued 'being seen quickly'. For example, they had strong preferences for shorter appointment waiting times and longer GP opening hours. People in the second class also valued shorter waiting times, but they had a strong general preference for HIV clinic rather than GP appointments. Conclusions: PLWHIV value many aspects of care for new health problems, particularly short appointment waiting times. However, they appear split in their general willingness to engage with GPs.